The Role of Emotion Regulation as a Mediator between Job Stress and Psychological Well-Being in Customer Service Employees - Mela Astri; Netty Jesajas; Muhammad Iqbal (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: Customer service employees operate in emotionally demanding environments characterized by high job demands, performance monitoring, and continuous interpersonal interaction. Such conditions potentially increase job stress and threaten psychological well-being. Objective: This study examines whether emotion regulation mediates the relationship between job stress and psychological well-being among customer service employees in Indonesia. Methods: A quantitative approach with a mediational correlational design was employed involving 258 customer service employees in Indonesia selected through purposive sampling. The research instruments included a job stress scale, the Emotion Regulation Questionnaire (ERQ), and the Psychological Well-Being (PWB) scale. Data analysis was conducted using path analysis via Hayes' PROCESS Macro Model 4. Results: Job stress was not significantly associated with psychological well-being (β = 0.0415, p > .05). Emotion regulation did not significantly predict psychological well-being and did not mediate the relationship between job stress and psychological well-being (95% CI [-0.0113, 0.0101]). Conclusion: The findings suggest that psychological well-being in this sector may be maintained by broader organizational and social resources rather than individual emotion regulation strategies alone.